Processamento reativo de blendas de amido termoplástico/poli(butileno succinato) (TPS/PBS) - Santos, Raul Franklin Andrade (Universidade Federal de São Carlos, 2022)
Thermoplastic starch is a natural and biodegradable polymer. However, it has some disadvantages attributed to its hydrophilic character, low mechanical properties and the phenomenon of retrogradation. These limitations can be overcome by mixing with biodegradable polyesters, as well as by chemically modifying the starch. In this context, blends of cassava starch with poly(butylene succinate) (PBS) and citric acid were processed in a Haake torque rheometer, followed by thermopressing. The processing speed varied at 80, 100 and 120 rpm. The content of added citric acid was 0, 1, 3 and 5 wt.%. For the gelatinization of starch, only glycerol was used as a plasticizer, in addition to its residual water. The samples were characterized by torque rheometry, water absorption measurements, water weight loss, contact angle, X-ray diffraction (XRD), scanning electron microscopy (SEM), infrared spectroscopy (FTIR-ATR) and visual analysis. The rheometry results demonstrated a decrease in torque in the presence of citric acid, indicating the occurrence of acid hydrolysis and/or the lubricating action of the acid. The percentage of water absorbed decreased with the increase in acid content, while weight loss increased, influencing the absorption results. The contact angle decreased for the acid-containing samples. In XRD, diffraction peaks associated with residual starch crystallinity were verified, while morphological analysis demonstrated the presence of native starch granules after gelatinization. Samples processed at 120 rpm and with higher acid content showed a more homogeneous morphology between phases. In FTIR, the functional chemical groups of the polymers that make up the blend were observed. Visually, the addition of citric acid caused a change in the color of the samples. Variation in mixing speed did not significantly influence the analysis results.
Reactive processing of thermoplastic starch/poly(butylene succinate) (TPS/PBS) blends
Keywords: Amido termoplástico; Poli(butileno succinato); Blenda; Thermoplastic starch; Poly(butylene succinate); Blend; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS